2017
DOI: 10.1016/j.psyneuen.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between biological markers of prenatal stress and infant negative emotionality are specific to sex

Abstract: HighlightsEffects of prenatal stress on fetal development may be mediated via glucocorticoids.We report that associations of prenatal cortisol with infant behavior are sex-specific.High maternal prenatal cortisol predicts increased negative emotionality in females.Alternatively, high cortisol predicts reduced negative emotionality in males.The same sex-interaction is evident for maternal salivary alpha-amylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 81 publications
7
37
0
Order By: Relevance
“…Braithwaite et al ( N  = 216) found a sex interaction such that 5-week-old girls exposed to maternal cortisol exhibited elevated negative emotionality, whereas cortisol-exposed boys exhibited attenuated negative emotionality [44•]. They then replicated this interaction effect in an independent sample ( N  = 88) of 2-month-old infants [50]. However, findings from the Queensland Flood Study ( N  = 121) showed an interaction with a contrasting pattern: disaster-related PNMS was associated with increased irritability in boys and was unrelated to irritability in girls [47].…”
Section: Resultsmentioning
confidence: 99%
“…Braithwaite et al ( N  = 216) found a sex interaction such that 5-week-old girls exposed to maternal cortisol exhibited elevated negative emotionality, whereas cortisol-exposed boys exhibited attenuated negative emotionality [44•]. They then replicated this interaction effect in an independent sample ( N  = 88) of 2-month-old infants [50]. However, findings from the Queensland Flood Study ( N  = 121) showed an interaction with a contrasting pattern: disaster-related PNMS was associated with increased irritability in boys and was unrelated to irritability in girls [47].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the literature just summarized, we would be remiss if we did not mention that some studies detect sex differences in the effects of prenatal stress on behavioral and physiological dysregulation (e.g., Braithwaite, Murphy, Ramchandani, & Hill, ). While not discussed in depth in this paper, it is likely that offspring sex plays a role in the mechanistic processes of prenatal programming (see Bale & Epperson, for review).…”
Section: Prenatal Stress and Behavioral–physiological Dysregulationmentioning
confidence: 99%
“…Regarding the literature just summarized, we would be remiss if we did not mention that some studies detect sex differences in the effects of prenatal stress on behavioral and physiological dysregulation (e.g., Braithwaite, Murphy, Ramchandani, & Hill, 2017).…”
mentioning
confidence: 99%
“…The effects of prenatal stress on female offspring depression-like behaviour are eliminated by adrenalectomy (2), consistent with risks mediated by glucocorticoid mechanisms that are specific to females. In the human literature, maternal prenatal cortisol, the main glucocorticoid hormone, has been associated with the following outcomes in females, but not males: reduced fetal growth, an established risk factor for later depression (4); increased infant negative emotionality (5,6); fearful infant temperament (7); affective problems in childhood (8); pre-adolescent anxiety (7), depression and a flattened diurnal cortisol profile in adolescence (9). In combination, these results present convincing evidence that exposure to prenatal cortisol increases risk of later affective symptoms in females.…”
mentioning
confidence: 99%
“…Animal models show that in utero exposure to elevated maternal glucocorticoids is associated with increased glucocorticoid receptor expression in the amygdala (12), structural changes in sub regions of amygdaloid nuclei (13) and associated depression-like behaviours in adult offspring (12). Human studies have demonstrated a female-specific association between prenatal stress and negative emotionality (5,6) and fearful temperament (7), which have been linked with amygdala activation. There is also direct evidence that elevated maternal cortisol in early, but not late, pregnancy is associated with a larger right amygdala volume in girls, but not boys (8).…”
mentioning
confidence: 99%